Potensi Limbah Biomassa Menjadi Karbon Aktif Sebagai Upaya Resources Recovery: Studi Literatur - Lutfi Adhi Setiapraja; Mohamad Rangga Sururi; Veny Rachmawati (Jurnal Serambi Engineering, 2024)
Reutilization of natural resources as a resource recovery effort is one aspect of sustainable development, one of which is the utilization of biomass waste. Biomass waste is waste from agricultural, plantation, livestock, and forestry processes that contain organic matter composed of carbon dioxide bonds, air, water, soil, and sunlight from plants and animals. Pollution by the accumulation or untreated biomasswaste will result in the potential formation of greenhouse gases (GHG). One of the efforts is to utilize biomass waste into activated carbon by carbonizing and activating the biomass waste. The indication of why biomass waste can be used as a material formaking activated carbon is because biomass waste contains lignocellulosic materials that have the ability to absorb metals and colors. The purpose of this paper is to see the potential of various kinds of biomass waste that can be utilized into activatedcarbon by conducting a journal review. The results of the review of various journals show that various kinds of biomass waste can be utilized into activated carbon. The lignocellulosic content of biomass waste consists of lignin in the range of 8%-53.85%,cellulose in the range of 6.92%-81%, and hemicellulose 11%-41%